Journey to glaucoma care – trusting but uncertain and uninformed: a qualitative study. (26th August 2019) - Lu, Thomas C; Semsarian, Caitlin R; White, Andrew; Dunn, Hamish; Angell, Blake; Ford, Belinda; Keay, Lisa
Abstract : Background: This study aims to explore patient perspectives regarding their journey to glaucoma care and sought to understand the determinants that guide their access to tertiary glaucoma care. Methods: Twenty‐nine patients who are glaucoma suspects or had definitive diagnosis of glaucoma were recruited from a large public glaucoma clinic and a private ophthalmology clinic in Sydney. Face‐to‐face, in‐depth semi‐structured interviews were conducted between April and December 2017. Interviews were recorded and transcribed verbatim. A framework method was used for thematic analysis of the data. Results: Thematic analysis resulted in the emergence of eight main themes. There was limited patient participation in decision making in their journey to glaucoma care. Consequently, there was great trust placed in the referring clinician. Patients valued their vision and therefore expressed a desire for high‐quality care. They placed considerable trust in their specialist but were often unsure how to evaluate the quality of care received. Patients lacked an understanding of the cost of glaucoma care and for some, cost remained a barrier to the access of private care. There were variable experiences with waiting times and the journey to clinic, with many patients making concessions and requiring support to access care. Conclusion: This study is the first qualitative study exploring the perspectives of glaucoma patients in Australia and the determinants of access to care. These findings support and can inform development of patient‐centred models of care furthering patient trust and empowerment.